(untitled) (Indonesian Minority Justice Review, 2025)
This paper investigates the legal struggles faced by the Madurese ethnic group in Kalimantan, focusing on both historical and contemporary legal discrimination that exacerbates ethnic tensions and impedes social justice. The Madurese, who have historically been marginalized in the region, have faced discriminatory legal practices that have perpetuated their social exclusion. The study examines how legal frameworks, such as the 1965 Anti-Communist Law, have historically been used to target the Madurese, especially during periods of political unrest, including the 1996 Sampit conflict. The paper also explores how contemporary legal issues—ranging from land ownership disputes to labor rights—continue to disadvantage the Madurese in Kalimantan, where they often face unequal treatment in the courts. Through an analysis of legal cases, interviews with community members, and examination of regional policies, the paper highlights how ethnic bias in the judicial system has hindered the ability of the Madurese to secure justice. The study underscores the need for judicial reforms aimed at combating ethnic bias, ensuring equal access to legal protections, and promoting social cohesion. The paper concludes by proposing specific measures for addressing ethnic discrimination within the legal system and ensuring that the Madurese and other marginalized groups have equal rights under the law.